Substance Use and Intimate Partner Violence: Clarifying the Relevance of Women’s Use and Partners’ Use - Golinelli, Daniela (2008)
Research has shown that when women and/or their partners are involved in substance use, women’s risk for intimate partner violence (IPV) is higher. Prior research has not examined whether substance use by both women and their partners contributes independently or interactively to women’s risk of victimization and has not identified factors moderating the effect of substance use by victim or partner. Mental health and social support are explored as moderators of the association between women’s victimization and substance use by victim or partner in a study of 590 impoverished women residing in the Los Angeles area. This study found that substance use by both the woman and her partner independently predicted IPV and that social support moderated the effect of women’s substance use. These findings clarify the relevance of substance use in the context of intimate relationships and that of social support as a buffer against IPV among impoverished women.